2020
DOI: 10.1007/978-3-030-45442-5_33
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Temporal Psycholinguistic Cues for Suicidal Intent Estimation

Abstract: Temporal psycholinguistics can play a crucial role in studying expressions of suicidal intent on social media. Current methods are limited in their approach in leveraging contextual psychological cues from online user communities. This work embarks in a novel direction to explore historical activities of users and homophily networks formed between Twitter users for extracting suicidality trends. Empirical evidence proves the advantages of incorporating historical user profiling and temporal graph convolutional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…In [25], authors applied Long short-term memory (LSTM) to detect mental illness from Reddit posts and achieved promising results. In [24], applied LSTM with attention mechanism to estimate suicidal intent by utilizing temporal psycholinguistic. We applied several pre-trained deep learning algorithms for multi-class mental illness detection such as Convolutional Neural Network, Gated recurrent unit (GRU), Bidirectional Gated recurrent units (Bi-GRU), LSTM, and Bidirectional LSTM.…”
Section: Deep Learning Methodsmentioning
confidence: 99%
“…In [25], authors applied Long short-term memory (LSTM) to detect mental illness from Reddit posts and achieved promising results. In [24], applied LSTM with attention mechanism to estimate suicidal intent by utilizing temporal psycholinguistic. We applied several pre-trained deep learning algorithms for multi-class mental illness detection such as Convolutional Neural Network, Gated recurrent unit (GRU), Bidirectional Gated recurrent units (Bi-GRU), LSTM, and Bidirectional LSTM.…”
Section: Deep Learning Methodsmentioning
confidence: 99%
“…Recent studies have focused on incorporating more social media components to capture as much available contextual information as possible. Among these are historical posts [4,[9][10][11][12][13][14][15][16][17][18], conversation trees [19], social and interaction graphs [4,10,12,17,20], user and post metadata information [10,11], and images [10]. While more contextual sources may be ideal for assessing an individual's mental health state, access to these data has become increasingly restrictive due to heightened data privacy concerns.…”
Section: Social Media Mental Health Classificationmentioning
confidence: 99%
“…Trifan Alina et al in [26] suggested a rule-based estimator using a tf-idf weighting technique for the bag-of-words characteristics to detect depression from the Reddit social media site. Mathur and Puneet in [27] proposed a solution using Bidirectional LSTM (BLSTM) + Attention model for the early detection of depression from the historic tweets of Twitter users.…”
Section: Literature Reviewmentioning
confidence: 99%